2009
DOI: 10.1038/ajg.2009.35
|View full text |Cite|
|
Sign up to set email alerts
|

A 25-Year Analysis of the American College of Gastroenterology Research Grant Program: Factors Associated With Publication and Advancement in Academics

Abstract: Introduction The American College of Gastroenterology (ACG) has awarded research grants for 25 years. We assessed the characteristics of grant recipients, their current academic status, and the likelihood of publication resulting from the grant. Methods Demographic data, year and amount of award, title of project, and recipient’s institution were extracted from ACG databases. Using ACG reports and medical literature search engines, we assessed publication based on grant-funded research, as well as career pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 10 publications
(11 reference statements)
1
18
0
Order By: Relevance
“…reported higher postaward federal funding for EM K‐awardees. Other specialty organizations, including gastroenterology, radiation oncology, dermatology, and surgery have found similar successes when solely evaluating award recipients . However, without a comparison arm, it is often unclear whether the grants significantly influenced the trajectories of already ambitious candidates .…”
Section: Discussionmentioning
confidence: 99%
“…reported higher postaward federal funding for EM K‐awardees. Other specialty organizations, including gastroenterology, radiation oncology, dermatology, and surgery have found similar successes when solely evaluating award recipients . However, without a comparison arm, it is often unclear whether the grants significantly influenced the trajectories of already ambitious candidates .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, publications resulted from 90% of the funded projects. 9 There are potential limitations of our study, including misclassification of outcomes obtained through the Internet-based search strategy. In an effort to minimize misclassification, we used dual review of the search results by independent committee members.…”
Section: Discussionmentioning
confidence: 96%
“…The most recent and extensive study was a 25-year review of a gastroenterology grant program [6]. Through a grant database and literature review, those authors concluded that 69% of their 255 awardees published based on their grant-funded research.…”
Section: Discussionmentioning
confidence: 99%